The Effect of Social Support on Academic Procrastination among University Students: The Mediating Roles of Intrinsic Learning Motivation and Resilience - Azra Fauziyah; Armiati Armiati (Universitas Negeri Padang, 2026)
Academic procrastination remains a common challenge in higher education, as it can lower academic achievement, reduce student engagement in the learning process, and delay the completion of studies. This study aims to analyze the effect of social support on academic procrastination among students at Universitas Negeri Padang by testing the mediating roles of intrinsic motivation to learn and resilience. This study utilized a quantitative approach with an explanatory design. A total of 396 students were selected through proportional random sampling from a population of 35,830 active undergraduate students. Data were collected using an online questionnaire and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results showed that social support had a significant negative effect on academic delay (β = −0.276, p < 0.001) and a positive effect on intrinsic learning motivation (β = 0.587, p < 0.001) and resilience (β = 0.504, p < 0.001). In addition, intrinsic learning motivation (β = −0.329, p < 0.001) and resilience (β = −0.219, p < 0.001) were also found to reduce academic procrastination. Indirect effect analysis confirms that these two variables mediate the relationship between social support and academic procrastination. In other words, students who receive greater social support tend to have higher levels of intrinsic motivation and resilience, making them better able to avoid academic procrastination. These findings expand the application of Self-Determination Theory by demonstrating that social support influences academic procrastination through motivational and psychological mechanisms. The results of this study provide guidance for universities to strengthen students’ resilience in order to reduce rates of academic procrastination.